Teachers’ Participation in Students’ and Staff’s Discipline in secondary schools as determinants of teachers’ Morale in Imo State - Chinyere Maryrose, NWACHUKWU, Ph.D; IHEANAETU, Beatrice Ifeyinwa, Ph.D; Gladys Chinyere ELEZUO, Ph.D (International Journal on Orange Technologies, 2020)
The study investigated the extent of teachers’ Participation in Students’ and Staff’s Discipline in secondary schools as determinants of teachers’ Morale in Imo State. The population of this study consisted of all 5047 teachers in the 275 public secondary schools in Imo State under the six (6) Education Zones. The study adopted Correlational Survey Design while simple random sampling technique was used in selecting the respondents. Data was obtained using a research questionnaire tagged “Participation in School Governance Questionnaire (PSGQ) and Teachers Morale Questionnaire (TMQ. Data obtained from the respondents was analysed using descriptive statistics (mean and standard deviation) while Pearson Product Moment Correlation analysis was used to test the hypotheses at 0.05 alpha levels. It was concluded that there is no significant relationship between teachers’ participation in staff’s discipline and morale of teachers in Imo State Secondary Schools. On the other hand, it was observed that there is significant relationship between teachers’ participation in students’ discipline and morale of teachers, in Imo State Secondary Schools. One of the recommended was that teachers should be allowed to participate in maintaining discipline among students and teachers, so that there will be a conducive environment for teaching and learning which will boost their morale as well as improving and promoting effective learning